A study of gynecological profile of patients undergoing hysterectomy with special reference to its indications - Suraneni, Pujitha Devi; Maharana, Sradhanjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy is the most frequently performed major gynecological surgical procedure, with millions of procedures performed annually throughout the world. Approximately 90% of hysterectomies are performed for benign conditions, such as fibroids causing abnormal uterine bleeding. Objective of the study was to study the gynecological profile of women undergoing hysterectomy. Methods: In this study 60 cases of hysterectomy were analyzed over a period of 2 years who underwent hysterectomy at Department of Obstetrics and Gynecology, Chalmeda Anand Rao Institute of Medical Sciences, Karimnagar. Informed consent was taken from all women. Detailed history, complete clinical, gynecological examination was carried out. Results: Maximum patients i.e. 56.7% were in the age group of 41-50 years followed by the age of 31-40 years i.e. 33.3%. Maximum number of hysterectomies were performed in Para 3. Maximum number of patients had menstrual problems which are about 63.3% and next more common complaint was discharge per vagina (53.3%). Of the 60 cases that underwent hysterectomies 40% of them are for abnormal uterine bleeding, 30% of them are for uterine fibroid, 15% of them are for endometriosis, 8.3% of them are for adenomyosis, 6.6% of them are for cervical dysplasia. Conclusions: The most common indication for hysterectomy was abnormal uterine bleeding.